2010
DOI: 10.1590/s1676-26492010000200008
|View full text |Cite
|
Sign up to set email alerts
|

IBE Promising Strategies Program 2008: "Epilepsy at School: Teaching the Teachers" - educational plan of the "Associação Brasileira de Epilepsia" with teachers of elementary school

Abstract: INTRODUCTION: The aim of this study is to evaluate trough questionnaires the knowledge about epilepsy of Elementary School teachers obtained in the "Promising Strategies Program 2008" from International Bureau for Epilepsy entitled "Epilepsy at School. Teaching the Teachers." performed by the official Brazilian branch "Associação Brasileira de Epilepsia" (ABE). METHODS: A questionnaire was developed by ABE and it is composed by 35 objective questions concerning the following areas: concepts and definition of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…People generally judge characteristics and behaviors of others relying on moral beliefs, cognitive processes and previous learning. [22][23][24] As recommended in other studies, 8,10 one of the strategies for reducing stigma and erroneous knowledge on epilepsy is continuing education. In our study, after the questionnaires, all education professionals attended a 4 hours course on epilepsy with basic topics about epilepsy, necessary for someone who will deal with students suffering from this condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People generally judge characteristics and behaviors of others relying on moral beliefs, cognitive processes and previous learning. [22][23][24] As recommended in other studies, 8,10 one of the strategies for reducing stigma and erroneous knowledge on epilepsy is continuing education. In our study, after the questionnaires, all education professionals attended a 4 hours course on epilepsy with basic topics about epilepsy, necessary for someone who will deal with students suffering from this condition.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The questionnaire contains 35 statements concerning the following topics: A -Concepts and definition of epilepsy and its causes (10 items); B -Treatment and adverse effects of antiepileptic medication (10); C -Popular stigma about epilepsy (5); D -Activities of people with epilepsy (PWE) (5); E -Firstaid during and after an epileptic seizure (5). Respondents were asked to indicate whether the statements were correct or wrong.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies used questionnaires from previous studies [36][37][38]: Elafros et al [36] used a threeitem assessment to assess felt stigma in Zambia [39], Eze et al [37] used a questionnaire adapted from a previous study of teachers' perception of epilepsy in Nigeria [40] to assess the trainee teachers' knowledge, attitudes and first aid management of epilepsy, and Tilahun et al [38] used a questionnaire assessing beliefs and social distance towards children with autism, adapted from the World Psychiatric Association's programme to reduce stigma and discrimination because of schizophrenia [41]. Eleven studies developed bespoke self-reported tools [42][43][44][45][46][47][48][49][50][51][52].…”
Section: Study Characteristicsmentioning
confidence: 99%